SWOT Analysis in Facing the Quality 2024 Elections at the Regional General Election Commission of Kubu Raya Regency, West Kalimantan - Heriyanto Heriyanto; Melti Oktavianda; Grace Kelly Hadiputri Sihombing (IHSA Institute, 2022)
This study aimed to identify internal and external factors at the Kubu Raya Regional General Election Commission and what strategies the Kubu Raya Regional General Election Commission took to prepare for the 2024 simultaneous elections. The research method used was the qualitative method. The study results indicate that as a government institution carrying out its primary duties and functions, the General Election Commission of Kubu Raya Regency is influenced by internal and external conditions. Internal conditions include Institutional, Human Resources, Leadership, Planning and Budgeting, facilities and infrastructure, as well as commitments built. Meanwhile, from the external aspect, it is influenced by the presence of stakeholders in the political field, the condition of the general public and related regulations and the strategies carried out by the arrangement of programs and activities of each work unit; Implementing employee arrangements in accordance with job analysis and employee workload analysis; Increasing the quality and quantity of HR of the General Election Commission of Kubu Raya Regency; Availability of an integrated performance management system; Optimizing the monitoring system and internal control over budget management; Implementation of activities under standard operating procedures (SOP); Availability and implementation of public service standards and notices; Availability of electoral logistics distribution maps; Improvement of modern office facilities and infrastructure; Optimizing the use of information technology; and Availability of an adequate budget ceiling.